Assessment of corneal biomechanics in anisometropia using Scheimpflug technology - Gao, Rongrong; Ren, Yuecheng; Li, Siheng; Xu, Huilin; Lin, Xuanqiao; McAlinden, Colm; Ye, Junming; Huang, Jinhai; Yu, Jinjin (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To investigate the relationship between corneal biomechanical and ocular biometric parameters, and to explore biomechanical asymmetry between anisometropic eyes using the corneal visualization Scheimpflug technology device (Corvis ST). Methods: 180 anisometropic participants were included. Participants were divided into low (1.00≤△Spherical equivalent (SE)<2.00D), moderate (2.00D≤△SE<3.00D) and high (△SE≥3.00D) anisometropic groups. Axial length (AL), keratometry, anterior chamber depth (ACD) and corneal biomechanical parameters were assessed using the OA-2000 biometer, Pentacam HR and Corvis ST, respectively. Results: The mean age of participants was 16.09 ± 5.64 years. Stress-Strain Index (SSI) was positively correlated with SE (r = 0.501, P < 0.001) and negatively correlated with AL (r = -0.436, P < 0.001). Some other Corvis ST parameters had weak correlation with SE or AL. Corneal biomechanical parameters except for time of first applanation (A1T), length of second applanation (A2L), deformation amplitude (DA), first applanation stiffness parameter (SP-A1) and ambrosia relational thickness-horizontal (ARTh) were correlated with ametropic parameters (SE or AL) in multiple regression analyses. A1T, velocity of first applanation (A1V), time of second applanation (A2T), A2L, velocity of second applanation (A2V), corneal curvature radius at highest concavity (HCR), peak distance (PD), DA, deformation amplitude ratio max (2mm) (DAR), SP-A1, integrated radius (IR), and SSI showed significant differences between fellow eyes (P < 0.05). There was no significant difference in asymmetry of corneal biomechanics among the three groups (P > 0.05). Asymmetry of some biomechanical parameters had weak correlation with asymmetry of mean corneal curvatures and ACD. However, asymmetry of corneal biomechanical parameters was not correlated with asymmetry of SE or AL (P > 0.05). Conclusion: More myopic eyes had weaker biomechanical properties than the contralateral eye in anisometropia. However, a certain linear relationship between anisometropia and biomechanical asymmetry was not found.